Advancing Pistacia terebinthus L. (Anacardiaceae) Research: Food Preservation, Functional Foods, and Nutraceutical Potential - Daniela Batovska (Foods)
Pistacia terebinthus L., commonly known as the turpentine tree, is a wild-growing species with a well-documented history of use in traditional medicine and ethnobotany. Various parts of the plant—fruits, seeds, resin, leaves, and galls—have demonstrated significant bioactive potential, particularly antioxidant, antimicrobial, and functional properties. Despite these promising attributes, the industrial application of P. terebinthus L. in contemporary food and nutraceutical systems remains limited and underexplored. Recent advances have employed a range of technological strategies—including encapsulation, active food packaging, emulsion stabilization, probiotic immobilization, and fermentation—to improve the stability, bioavailability, and functional performance of P. terebinthus L.-derived extracts within food matrices. These approaches have shown potential in enhancing aroma retention, extending shelf life, and supporting probiotic viability, thereby positioning P. terebinthus L. as a promising candidate for use in functional formulations and natural food preservation. Nevertheless, further investigation is required to optimize processing parameters, assess the long-term stability of bioactive compounds, and establish standardized regulatory frameworks. Addressing these challenges will be essential for facilitating the broader integration of P. terebinthus L. into the functional food, nutraceutical, and food preservation industries.